2019
DOI: 10.1007/s40262-019-00735-7
|View full text |Cite
|
Sign up to set email alerts
|

Voriconazole: A Review of Population Pharmacokinetic Analyses

Abstract: Numerous population pharmacokinetic studies on voriconazole have been conducted in recent years. This review aimed to comprehensively summarize the population pharmacokinetic models for voriconazole and to determine which covariates have been identified and which remain to be explored. We searched the PubMed and EMBASE databases from inception to March 2018 for population pharmacokinetic analyses of voriconazole using the nonlinear mixed-effect method. A total of 16 studies were included in this review, of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
35
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 62 publications
4
35
0
1
Order By: Relevance
“…Therefore, inclusion of covariates would not have been highly informative. Previous plasma population models for voriconazole vary between the studies, in terms of PK compartments (one or two compartments), identified covariates, and PK parameter estimates (Shi et al, 2019). Amongst these studies, parameters from our study were comparable to those from Pascual et al (Pascual et al, 2012), who fitted a onecompartment model with the first-order absorption and first-order elimination to 505 plasma voriconazole concentrations from 55 adult patients.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Therefore, inclusion of covariates would not have been highly informative. Previous plasma population models for voriconazole vary between the studies, in terms of PK compartments (one or two compartments), identified covariates, and PK parameter estimates (Shi et al, 2019). Amongst these studies, parameters from our study were comparable to those from Pascual et al (Pascual et al, 2012), who fitted a onecompartment model with the first-order absorption and first-order elimination to 505 plasma voriconazole concentrations from 55 adult patients.…”
supporting
confidence: 60%
“…cytochrome P450 2C19 genotype and liver function (e.g., ALT and AST) (Shi et al, 2019). Due to the high risk of selection bias, it is recommended to avoid stepwise covariate modeling for inclusion of statistically significant covariates in small data sets (<50-100 subjects), especially if the aim of the analysis is predictive modeling (Ribbing and Jonsson, 2004).…”
mentioning
confidence: 99%
“…The mechanism behind the interaction with CYP450 inhibitors, omeprazole, and voriconazole is via CYP2C19 and CYP3A4 inhibitors [ 4 , 38 , 39 ]. On the one hand, the effect of PPIs on the PK of voriconazole depends on the dose and kind of PPIs, and how these factors affect various capabilities of CYP2C19 [ 12 , 36 ]. On the other hand, a recommendation specific to omeprazole 20 mg/day stated that this drug and dosage did not significantly affect voriconazole levels, which was similar to our study [ 4 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Voriconazole is mainly metabolized by CYP2C19 [ 4 , 11 ]. Therefore, high variability in the PK of voriconazole can be caused by CYP2C19 polymorphism [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], and these gene polymorphisms cause variations in drug clearance. Clinical factors that have been reported to affect the PK of voriconazole include body weight [ 15 , 16 , 20 , 22 , 23 ], age [ 18 , 19 ], liver function [ 20 ], aspartate aminotransferase (AST) [ 14 ], direct bilirubin (DB) [ 24 ], and voriconazole taken concurrently with CYP2C19 inducers (rifampin) [ 13 , 25 ], and inhibitors (proton pump inhibitors; PPIs) [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation